Design and synthesis of the superionic conductor Na10SnP2S12 - William D. Richards (Nature Portfolio, 2016)
Solid electrolytes are an attractive alternative to the flammable organic solvents typically used in intercalation batteries. Here, the authors report the computation-assisted discovery and synthesis of Na10SnP2S12, a sodium electrolyte with room temperature conductivity of 0.4 mS cm−1.